Arah Kebijakan Militer Arab Saudi di Bawah Komando Mohammed Bin Salman (MBS) Menghadapi Visi Saudi 2030 - Ali, Muhammad; Rofii, Muhammad Syaroni, Mr. (UI Scholars Hub, 2021)
The Saudi Arabia's Grand Vision 2030 which has been launched since 2016, but Saudi Arabia's involvement in the political arena in the Middle East has drained the finances of this rich country. Saudi Arabia actually wants to get out of the mud of conflict in the region and find a way to save face under de facto of the Prince Mohammed bin Salman (MBS) leadership. The larger goal of Saudi Vision 2030 is more important than maintaining its regional hegemony under the shadow of the United States. MBS's policy of involving Saudi Arabia, which is supported by the United States and the West in regional conflicts in Syria, Yemen, Libya, Iraq, and Qatar, has proven to be inconsistent with expectations because it is hampered by the activeness and effectiveness of Iranian proxies. To what direction of Saudi Arabia's military policy in the Middle East region to face Saudi Vision 2030, under his Command as a Minister of Defense, MBS can regulate the rhythm of Saudi Arabia's military policy while, at the same time, maintaining its hegemony in the region with military independence and reducing the intensity of military involvement in regional conflict zones and trying to normalize relations with Iran and Turkey so that they can focus on the Saudi vision program 2030. Keywords: Vision, Saudi Arabia,military, hegemony, regional.